The gym teacher from the Black Lagoon - Thaler, Mike; Lee, Jared D. (New York : Cartwheel Books : Scholastic, 2008)
On the first day of school, a young boy expects only the worst when he discovers that his new gym teacher is "Coach Kong," Mr. Green.
"This edition, first printing, September 2008" -- T.p. verson.
Keywords: School children